Dari halaman rumah ke hadapan layar: Pola bermain dan fungsinya kepada perkembangan kanak-kanak - Fatimah Abdullah; Norulhuda Sarnon@Kusenin; Suzana Mohd Hoesni; Wan Azreena Wan Jaafar (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
Children are the asset of a family. They are also considered as an important asset to a country because they are considered as future leaders. Thus, children should not only be intelligent but also possess particular skills. One of the ways to develop the particular skills is through play activities. Unfortunately, recently, group play patterns in the lawn, in particular has changed to individual play which takes place in front of the televisyen screen or computer within the household or in separate rooms. This practice definitely has left an important influence to the children’s development. This study was carried out in 2007. Therefore, this article discusses the issues relating to the patterns and functions of play from the past until recently on children’s development. The issue raised in this paper is to discuss on the existing causes of changes. What are the implications on the existing changes towards the development and well being of children? How can the changes be handled? What is the function of the family, community and country in dealing with the related issue? This article is based on secondary data from library research were analyzed inductively. Findings indicated that generally, play is crucial for children’s physical, cognitive, social and emotional development. Conversely, the change in the play pattern which specifically involves video and computer screens gives a different implication. Positive and negative implications depended on the type of software used. Screen play in the form of aggression is related to negative behavior, whereas educational play is related to positive implication. Consequently, the role of adults is to monitor children’s play activities